Fikir ve Sanat Eserlerinin Ceza Hukuku Kapsamında Korunması - Oğurlu, Cüneyt Şamil (Fatih Sultan Mehmet Vakıf Üniversitesi, Lisansüstü Eğitim Enstitüsü, 2019)
Dünya çapında teknolojik ve kültürel gelişmeler, fikri mülkiyetin her zamankinden daha fazla korunması ihtiyacını doğurmuştur. Fikri mülkiyetin korunması, ülkelerin gelişmişlik düzeyi ile de ilgilidir. Bu nedenle Türkiye'de de özellikle sınai mülkiyet ve telif hakları alanındaki önceki düzenlemelere ek olarak Avrupa Birliği Müktesebatı uyum sürecinde yasal düzenlemeler yapılmıştır. Fikri haklar, Özel Hukuk ve Ceza Hukuku alanında hukuken korunmaktadır. 5846 Sayılı Fikir ve Sanat Eserleri Kanunu'nda düzenlenen cezai hükümler, eser sahibinin mali ve manevi haklarına tecavüzün önlenmesine ve bağlantılı hak sahiplerinin haklarına tecavüzün önlenmesine yönelik düzenlemelerdir. Korsan yayın yoluyla telif hakkı ihlalleri, bandrol alma yükümlülüğüne aykırılık fiilleri, veri tabanları aleyhine işlenen suçlar gibi eylemler ülkemizde bu kanuni korumaya rağmen tam olarak önlenememekte, fikri mülkiyet haklarının istenildiği şekilde korunması halen tam olarak sağlanamamaktadır. Mevzuatta birçok değişikliği içeren Fikir ve Sanat Eserleri Kanununda yapılan değişiklikler halen Mecliste yasalaşmayı beklemektedir. Bu çalışmada fikri mülkiyetin 5846 sayılı Kanun kapsamındaki korunması, Kanun Tasarısı, yargı kararlarıyla birlikte incelenmiştir.

Worldwide technological and cultural developments have created the need to protect intellectual property more than ever. The protection of intellectual property is also related to the level of development of countries. Thus, beside the previous regulations in the field of industrial property and copyrights, legal arrangements have been made in order to harmonize with the European Union acquis. Intellectual property rights are legally protected in the field of private and criminal law. These crimes in the Turkish Penal Code are: Violations of the Owner's Financial Rights, Violations of the Owner's Spiritual Rights, Violation of the Provisions for the Prevention of Violation of Rights, Violations of Rights of Linked Rights Holders, Copyright Infringements via Pirated Publications, Offenses against Bandrol Liability, Crimes Against Databases. Despite this legal protection in Turkey, there are still difficulties in the full protection of intellectual property and the legislation is not sufficient to prevent pirated publications. A Law on Intellectual and Artistic Works covering many changes is waiting to be enacted in the Turkish National Assembly. The penal clauses in the Law No. 5846 on Intellectual and Artistic Works are arrangements for the prevention of violations against financial and moral rights of the author and for the prevention of infringement of the related rights of the holders. The acts such as copyright violations, violations of the obligation to take a bandrol, and relevant crimes against databases are not precluded precisely in Turkey despite this wide legal protection. So, intellectual property rights are still not fully protected as ıntented. In this study, the protection of intellectual property within the scope of Law No: 5846 was examined together with judicial decisions.
Protection of itellectual and artistic works within the scope of criminal law
Keywords: Fikri Hak; Mali Haklara Tecavüz; Fikir ve Sanat Eseri; Manevi Haklara Tecavüz; Bağlantılı Hak; Bandrol Yükümlülüğü; Telif Hakkı İhlali; Korsan Yayın; Korsan Kitap; Intellectual property rights; Intellectual and Artistic Works; Crimes against intellectual property rights; Bandrol Liability; Copyright Infringement; Pirated Publication; Illegally Printed Book